2012
DOI: 10.1021/nn204600d
|View full text |Cite
|
Sign up to set email alerts
|

Determining Peptide Sequence Effects That Control the Size, Structure, and Function of Nanoparticles

Abstract: The ability to tune the size, shape, and composition of nanomaterials at length scales <10 nm remains a challenging task. Such capabilities are required to fully realize the application of nanotechnology for catalysis, energy storage, and biomedical technologies. Conversely, nature employs biomacromolecules such as proteins and peptides as highly specific nanoparticle ligands that demonstrate exacting precision over the particle morphology through controlling the biotic/abiotic interface. Here we demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
84
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 27 publications
3
84
0
Order By: Relevance
“…It has been reported that where peptidepeptide interactions take place forming multilayers, adsorption energies of single peptides can greatly be diminished. 40 Thus, for this system a direct link between thermodynamic changes and the differences observed in morphology modification in the presence of peptides was difficult to obtain. However, ITC allowed direct characterization of ZnO-ZnO-BP interactions and the quantification of energetic changes occurring during the adsorption process.…”
Section: Itc Study Of Interactions Of G-12 and Gt-16 Withmentioning
confidence: 96%
“…It has been reported that where peptidepeptide interactions take place forming multilayers, adsorption energies of single peptides can greatly be diminished. 40 Thus, for this system a direct link between thermodynamic changes and the differences observed in morphology modification in the presence of peptides was difficult to obtain. However, ITC allowed direct characterization of ZnO-ZnO-BP interactions and the quantification of energetic changes occurring during the adsorption process.…”
Section: Itc Study Of Interactions Of G-12 and Gt-16 Withmentioning
confidence: 96%
“…57 Further investigations have been carried out by the same group in order to identify the structural motifs present in the peptides that actually prevent the nanoparticles from agglomerating, and to fine-tune the size, surface structure, and functionality of single-crystal Pd-NPs between 2 nm and 3 nm using materials directing peptides. 58,59 A special class of compounds that merits separate mention is solvents known as ionic liquids (ILs): ionic compounds that exhibit fluidity at ambient temperatures. 60 ILs can stabilize metal nanoparticles by different mechanisms, intrinsically as well as through the addition of secondary stabilizers.…”
Section: Protection Of Catalytic Nanoparticles Against Agglomerationmentioning
confidence: 99%
“…Previous reports show that when peptides were used as templates for PdNP fabrication, the amino acids, including histidine, arginine, and asparagine residues, with nitrogen-containing groups in the side chain play an important role in the coordination with Pd. [15] Therefore, we fabricated a polypeptide chain labeled with a fluorescent dye tetramethylrhodamine (TAMRA) as another bioprobe (TAMRA-GLVPRGSNNHHD). The incubation of the dye-labeled peptide (85 nm) with PdNPs resulted in the quenching of TAMRA emission, with the quenching degree dependent on the amount of PdNPs (Figure 4 a).…”
mentioning
confidence: 99%